2007
DOI: 10.1111/j.1365-313x.2007.03063.x
|View full text |Cite
|
Sign up to set email alerts
|

ROS production and protein oxidation as a novel mechanism for seed dormancy alleviation

Abstract: SummaryAt harvest, sunflower (Helianthus annuus L.) seeds are dormant and unable to germinate at temperatures below 15°C. Seed storage in the dry state, known as after-ripening, is associated with an alleviation of embryonic dormancy allowing subsequent germination at suboptimal temperatures. To identify the process by which dormancy is broken during after-ripening, we focused on the role of reactive oxygen species (ROS) in this phenomenon. After-ripening entailed a progressive accumulation of ROS, namely supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
380
2
11

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 447 publications
(413 citation statements)
references
References 74 publications
(161 reference statements)
20
380
2
11
Order By: Relevance
“…The mode of action of cyanide in stimulating seed germination remains unclear but is thought to involve reactive oxygen species 32,39 . It has also been proposed that cyanide acts at an initial step in dormancy alleviation and nitrogen oxide is required at a later step 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The mode of action of cyanide in stimulating seed germination remains unclear but is thought to involve reactive oxygen species 32,39 . It has also been proposed that cyanide acts at an initial step in dormancy alleviation and nitrogen oxide is required at a later step 33 .…”
Section: Discussionmentioning
confidence: 99%
“…, H 2 O 2 contents Superoxide anion content was determined according to the method developed by Elstner and Heupel (Oracz et al, 2007). One gram of outermost whorl petals was ground with liquid nitrogen.…”
Section: Measurements Of O 2 -mentioning
confidence: 99%
“…There is new information on the fate of oxidized proteins from investigations that link protein oxidation and autophagy (Bassham, 2007;Xiong et al, 2007aXiong et al, , 2007b and describe the role of protein oxidation in seed dormancy (Oracz et al, 2007). It was found that protein oxidation is followed by controlled degradation and recycling and that these processes are essential for cellular viability, signaling, development, and recovery from oxidative stress.…”
Section: New Perspectives On Ros Scavengingmentioning
confidence: 99%